Pattern of hmlh1, hmsh2 and hmsh6 expressions and clinical characteristics in Malaysian colorectal carcinoma cases / Khoo Joon Joon - Khoo, Joon Joon (2011)

(untitled)
Many environmental factors and genetic risk factors have been implicated in the development of colorectal carcinomas. Several genetic mechanisms of tumorigenesis had been suggested i.e. the suppressor and the mutator pathways. The suppressor pathway constitutes inactivation of tumour suppressor genes: p53, APC (adenomatous polyposis coli) and DCC (deleted in colorectal cancer) genes or the activation of proto-oncogene: k-ras. The mutator pathway consists of inactivation of mismatch repair (MMR) genes which results in inability to repair mismatched DNA (deoxyribonucleic acid) bases during replication. The aims of the study were to determine the incidence and pattern of mismatch repair defect by immunohistochemistry in a sample of Malaysian colorectal carcinoma cases and correlate this to the clinical and pathological features. Additionally, the relationship between p53 over-expression and the mismatch repair status of the tumours were analysed. Materials and Methods: The clinical and demographic characteristics of 298 patients with colorectal carcinomas and the histomorphology of their tumours were studied. Analyses of the mismatch repair genes as well as mutation of the tumour suppressor gene were determined by immunohistochemical methods using antibodies against hMLH1, hMSH2 and hMSH6 proteins; and p53 respectively. Results: The ratio of male to female patients with colorectal carcinomas was 1.26:1. Their age ranged from 25 to 91 years (mean of 61 years). There was an overall predominance of left sided lesion (69.5%). Forty three out of 298 cases (14.4%) showed abnormal staining viii pattern for at least one mismatch repair proteins with majority of cases (65.1%) showing single hMLH1 loss. About half of the colorectal carcinomas (50.7%) were associated with p53 over-expression. 92.7% of tumours with p53 over-expression did not have any mismatch repair defect (MMR-d) and 74.4% of MMR-d tumours did not show any p53 over-expression (p<0.001). Tumours with mismatch repair defect were located frequently at the right side of colon (p<0.001) while tumours showing p53 over-expression were significantly left sided (p<0.001). MMR-d tumours were more likely poorly differentiated carcinomas (p<0.001), produced larger amounts of mucin (p=0.007), showed exophytic growth (p=0.007) and were bigger in size (p=0.002) than tumours with no mismatch repair defect. However, there was no significant difference in age at presentation, gender, race or survival for patients with MMR-d tumours compared to patients without the defect. Discussion and Conclusion: In this study there were 14.4% of colorectal carcinoma cases with mismatch repair defect, which was comparable with that found worldwide (7 to 20%). The patients with MMR-d colorectal carcinomas had distinct clinical and pathological features. Immunohistochemical staining for MMR-d should be done on these selected cases. This information on the MMR-d status will definitely help clinicians in their management of the patients. There was a significant inverse correlation between loss of MMR-d protein and p53 over expression. MMR-d tumours and tumours with p53 over-expression also arose in significantly different anatomical sites. This supported the suggestion that there are at least two different pathways of colorectal carcinogenesis: the suppressor gene pathway and MMR gene inactivation (mutator) pathway.